Adaptation of the Toba Batak community in conservation of the Lake Toba environment - Ulung Napitu; Corry Corry; Hasian Napitu; Ratoga Ambarita; Beresman Sihola; Friska Panjaitan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to examine the adaptation of the Toba Batak community in the preservation and maintenance of the Lake Toba environment in Samosir Regency. The occurrence of environmental damage to Lake Toba is due to the behavior of the Toba Batak community influenced by its socio-cultural values towards the Lake Toba environment. To re-maintain the Lake Toba environment, the Toba Batak community must adapt to the changing environment of Lake Toba. The method used in this research is a qualitative research method. With qualitative methods, researchers conducted in-depth interviews with informants, namely the Toba Batak community in Samosir Regency. The informants interviewed in this study were 13 people representing community leaders, religious leaders, government, NGOs, and environmental activists living in Samosir Regency. In addition to conducting in-depth interviews, researchers also carried out participatory observation and literature study. The results show that the occurrence of environmental damage to Lake Toba is due to the behavior of the Toba Batak people who are influenced by maladaptive socio-cultural values to the Lake Toba environment. Efforts taken for the preservation and maintenance of the Lake Toba environment, in addition to repositioning cultural values that are counterproductive to environmental preservation, also develop the cultural values (local wisdom) of the Toba Batak that are adaptive to the Lake Toba environment